2013
DOI: 10.1007/s00420-013-0848-y
|View full text |Cite
|
Sign up to set email alerts
|

The incremental effect of psychosocial workplace factors on the development of neck and shoulder disorders: a systematic review of longitudinal studies

Abstract: While we found evidence for an incremental effect of different psychosocial work factors (in addition to the effect of physical job factors), these results have to be interpreted carefully in order to support the notion that psychological factors can have an independent causal influence on the development of musculoskeletal disorders. Nevertheless, our findings are important for the development of preventive strategies, as they stress the need for preventive approaches that tackle both physical and psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
3
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 45 publications
8
75
3
8
Order By: Relevance
“…High job strain was significantly associated with symptoms in both the lower back (OR 1.38, 95%CI 1.07-1.78) and neck/shoulder (OR 1.33, 95%CI 1.08-1.62). These findings accord with those from another recent systematic review which included 18 prospective longitudinal studies of neck/shoulder disorders [97]. The authors concluded that there was strong evidence for adverse effects of high job demands, low job control, low social support and high job strain.…”
Section: Associations With Musculoskeletal Illnesssupporting
confidence: 78%
“…High job strain was significantly associated with symptoms in both the lower back (OR 1.38, 95%CI 1.07-1.78) and neck/shoulder (OR 1.33, 95%CI 1.08-1.62). These findings accord with those from another recent systematic review which included 18 prospective longitudinal studies of neck/shoulder disorders [97]. The authors concluded that there was strong evidence for adverse effects of high job demands, low job control, low social support and high job strain.…”
Section: Associations With Musculoskeletal Illnesssupporting
confidence: 78%
“…It has been shown that high job demands, low job control and social support, as well as job strain are associated with the development of neck and/or shoulder disorders (Kraatz et al 2013). Additionally, psychosocial stressors have significant effects on the development of musculoskeletal problems in longitudinal studies with follow-ups ranging from 1 to almost 30 years (Lang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Some other prospective studies have reported significant associations between psychosocial stressors and development of musculoskeletal problems, but the follow-up periods in those studies have been relatively short (Kraatz et al 2013;Lang et al 2012). Previous studies with follow-up periods of 10 years or more have suggested that workrelated stress (Brage et al 2007), low job control (KailaKangas et al 2004), and mental overstrain (Leino and Hänninen 1995) may lead to musculoskeletal pain and hospitalization, sickness absence, rehabilitation, or disability pension due to musculoskeletal disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a consistent standardised diagnostic approach has possibly hindered our understanding of the extent of the problem in the workplace and across countries, and consequently the development of effective interventions and preventive tools to reduce the burden of musculoskeletal pain, including shoulder problems [29,31]. With this in mind, there have been a number of initiatives to try to improve diagnostic classification of upper limb disorders.…”
Section: Specific Shoulder Disorders and Non-specific Painmentioning
confidence: 99%
“…A more recent review of 18 longitudinal studies of psychosocial workplace factors on the development of neck and shoulder disorders found evidence for a cumulative effect of high job demands, low job control, a lack of social support and job strain on the incidence of symptoms [31]. The authors confined the review to prospective studies that took account of at least one physical workplace exposure because they reasoned that workers are not exposed to psychosocial factors in isolation, but rather a combination of physical and psychosocial aspects of work simultaneously.…”
Section: Occupational Psychosocial Risk Factorsmentioning
confidence: 99%